The Women's Empowerment in Agriculture Index is used by development organizations to improve women’s empowerment - CGIAR Research Program on Policies, Institutions, and Markets (2019)
The Women's Empowerment in Agriculture Index and several variations of the index developed since 2012 (Project WEAI, Abbreviated WEAI, WEAI for value chains) have been used by 103 organizations in 54 countries, including the Inter-American Development Bank and the NGO Swisscontact.